Prognostic and predictive values of the grading system of lymph node status in patients with advanced-stage gastric cancer - Zhang, Xue-Mei; Shen, Wei-Wei; Song, Ling-Jun (Frontiers in Oncology, 2023)
Background: Lymph node metastasis is one of the most important prognostic factors of gastric cancer. However, the effect of germinal centers in lymph nodes on the prognosis of patients with gastric cancer has not been reported. This study aimed to investigate the contribution of germinal center generation to prognostic parameters and clinicopathological significance in gastric cancer. Methods: We retrospectively reviewed gastric cancer patients who underwent surgery from October 2012 to June 2022. We analyzed 5484 lymph nodes (210 patients) and calculated the lymph node metastasis rate (LNMR) and the proportion of non-metastatic lymph nodes containing three or more germinal centers (NML-GCP). Results: Using a grading system that incorporated LNMR and NML-GCP. The tumors were classified into three groups based on this system, which was found to be significantly associated with prognosis. The TNM stage and grading system of lymph node status were independent risk factors for overall survival (OS) and disease-free survival (DFS). The 5-year OS rates for patients with advanced gastric cancer were 85.07% (n=50), 58.34% (n=42), and 24.44% (n=21) for Grades 1, 2, and 3, respectively (p<0.0001). The 5-year DFS rates were 65.32% (n=58), 40.85% (n=51), and 5.88% (n=34), respectively (p<0.0001). Patients with Grade 1 advanced gastric cancer had higher 5-year OS and DFS rates compared to those with Grade 2 or 3 in TNM stage II and III. Furthermore, the 5-year OS and DFS rates differed significantly among patients with different grades of advanced gastric cancer who received chemotherapy (p<0.0001). Conclusions: These findings suggest that the grading system may be valuable for predicting prognosis and guiding clinical management in patients with gastric cancer, and provides good prognostic stratification for OS and DFS in patients with TNM stage II and III.